The use of English as a lingua franca in translation - Foley, J. A.; Deocampo, M. F. (Universitas Pendidikan Indonesia, 2016)
In translation, not only two languages but two cultures come into contact which means that translators must consider who wrote the text, when, why, for whom and who is now reading it and for what purpose. In the wake of rapid technological advances and the need to spread information quickly and efficiently, translation has grown in importance in the globalized world. So has its reliance on English in its role as a global lingua franca. English is often being used for ‘interculturalizing’ native languages but it is also true that English texts are written by speakers who use English as a lingua franca (ELF) with the additional consequence of local languages being incorporated into the texts. This is the linguistic hybridity used in constructing a wider view of the world. However, the prime aim of any lingua franca communication is mutual intelligibility. Saussure wrote about the contrasting principles of provincialism (ésprit de clocher) and what he termed intercourse: the need for broader communication. We can see Saussure’s principles as two imperatives: the cooperative and territorial imperatives. That is to say that language change is brought about by the ‘cooperative imperative’ as we need to continually modify our language in order to communicate with other people. At the same time, there is the ‘territorial imperative’ to secure and protect our own space and sustain our separate social and individual identity. In this study, the translation of linguistic units can only be understood when considered together with the cultural contexts in which they arise, and in which they are used. Blogging in Singapore and the Philippines is part of the ‘cooperative and territorial imperatives’ where the use of English as a lingua franca is intertwined with translanguaging.